Paisagens literárias de Belo Horizonte: concreto e sensível - Iara Lopes Nogueira Coelho (2023)
Since its foundation, Belo Horizonte has experienced great transformations, when the once small Arraial do Curral Del Rei was converted into the new capital of the State of Minas Gerais. The modernization processes and the transformations of the landscapes that followed them are known through official historical documentation. However, in addition to these records, singularities of the city’s history are also preserved in the literary production about it. In the composition of its narratives, literature can present unique landscapes, understood as a sensorial set that explains the subject’s perception of the world. This is the guiding thread that structures this thesis. The case study focuses on the landscapes of Belo Horizonte present in selected works by João Alphonsus and Carlos Drummond de Andrade, through which it becomes possible to create an approximation with the city of the first half of the 20th century, in representation, and, with this, they perpetuated the landscapes through explorations that allow access not only to the visible elements, but to the set of stimuli when also sounds, textures, smells and tastes are conceived as fundamental parts of the construction of the experience in the landscape. Thus, the objective of the research is to direct observations to the landscapes constructed by them within their writing and imagination structures, so that it is possible to foster a landscape theory in line with literature. The sensitive contact with the city presented in the chosen works unfolds through the rescue of the porous matter of everyday life, recovering, in daily gestures, unique versions of the world.